The The relationship between sociology and economics (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
It is evident for every researcher in social sciences that there is a close interrelationship between them and the economic aspect. For example, political relations in any country are governed by the economic aspect through working conditions, consumer debt, community welfare, tax rates, and many other economic factors.Social life in general consists of a number of religious, political, economic, family and educational aspects, each of which affects others in the field of work. For example, workers belonging to a particular religious or social group may reduce their productivity rates if the administration abuses them in dealing with them in achieving their just goals.Sociology is considered one of the sciences that have a great impact on society through its many branches, such as religious sociology and educational sociology... in addition to the rest of the other branches that intertwine among themselves and influence each other and this is what is known as economic sociology, whose scholars belong to a number of knowledge branches are experts in labor relations, sociologists, industrial psychologists, demographics, and economic anthropologists, in addition to other branches of sociology, such as the professions, development, work, formal organizations, and others, and allof this is closely related to the economy.The study aimed to clarify the relationship between economic sociology and both economics and sociology. The study concluded that economic sociology came as a result of sociology’s failure to explain economic phenomena related to man in an accurate interpretation and to prepare ways to solve the dilemmas facing society, and also the failure of economics in analyzing economic phenomena and studying their reflections on society. This shortcoming led to the emergence of economic sociology, which combined the two sciences and set rules for studying social and economic phenomena at the same time.